2021
DOI: 10.1002/mp.15411
|View full text |Cite
|
Sign up to set email alerts
|

The detective quantum efficiency of cadmium telluride photon‐counting x‐ray detectors in breast imaging applications

Abstract: Purpose In breast imaging applications, cadmium telluride (CdTe) photon counting x‐ray detectors (PCDs) may reduce radiation dose and enable single‐shot multi‐energy x‐ray imaging. The purpose of this work is to determine the upper limits of the detective quantum efficiency (DQE) of CdTe PCDs for x‐ray mammography and to compare them with the published DQEs of energy‐integrating detectors (EIDs) and other PCDs. Methods We calibrated and validated a Monte Carlo (MC) model of the DQE of CdTe PCDs using an XCount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The simulation model presented is an extension of the model presented in our previous work. 6 Similarly this model was based on an XCounter Thor CdTe PCD with a 750um thick active layer and 100um pixel pitch with charge summation enabled.…”
Section: A the Simulation Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The simulation model presented is an extension of the model presented in our previous work. 6 Similarly this model was based on an XCounter Thor CdTe PCD with a 750um thick active layer and 100um pixel pitch with charge summation enabled.…”
Section: A the Simulation Modelmentioning
confidence: 99%
“…Unlike our previous work 6 the input energy spectrum is not generated using the Tucker and Barnes algorithm 10 until image quality metrics were calculated. Similar to the approach by Persson et al 11 , the input energy spectrum is a series of mono-energetic sources from 10 keV to 50 keV in 0.5-keV increments.…”
Section: Monte-carlo Stagementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we recently showed that the spatial resolution of CdTe PCDs is expected to be superior to that of slot-scanning silicon PCDs. 11 Ghammraoui et al 12 investigated CdTe detectors for breast density mea-surements, and Ding et al 13 investigated cadmium zinc telluride for measurement of the water, lipid, and protein content in breasts, but there has been little work on CdTe for CESM.…”
Section: Introductionmentioning
confidence: 99%